Management of Glyphosate Isopropylamine-Resistant Goosegrass (Eleusine indica) Biotypes Through Pre- and Post-Emergence Herbicides - Koko Tampubolon; Edison Purba; Mohammad Basyuni; Diana Sofia Hanafiah (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis)
The resistance status of Eleusine indica to the isopropylamine glyphosate herbicide leads to control losses in oil palm plantations. Appropriate management is needed to reduce the presence of glyphosate-resistant E. indica. This study aimed to obtain the recommended sequence or pattern of pre- and post-emergence herbicides in controlling glyphosate-resistant E. indica biotypes. This study was conducted in Telaga Sari Village, Sunggal Subdistrict, Deli Serdang District, North Sumatra, Indonesia from January to August 2019. The seeds were used from a confirmed highly glyphosate-resistant biotype of E. indica at 1,080 g ai ha-1. This study used the factorial Randomized Block Design with four replications. The first factor was the type of pre- and post-emergence herbicides at 1 l ha-1, respectively. The second factor was E. indica biotypes. Parameters were analyzed by ANOVA and subsequently followed by DMRT at P < 0.05 with IBM SPSS. Results showed that pre-emergence herbicides were more effective in controlling biotypes of glyphosate-resistant E. indica or were classified as excellent than post-emergence at the similar dose. The percentage capability of pre-and post-emergence herbicides in sequence were indaziflam or oxyfluorfen > pendimethalin > propaquizafop > potassium glyphosate > mesotrione. The herbicide performance of propaquizafop was classified as very good compared to other post-emergent herbicides.